A qualitative meta-synthesis about challenges experienced in occupational therapy practice. (September 2015) - Murray, Carolyn; Turpin, Merrill; Edwards, Ian; Jones, Mark
Introduction: Information about challenges for occupational therapists is typically provided in small-scale studies from different perspectives. The purpose of this meta-synthesis was to synthesise and report about challenges in occupational therapy practice that appear to penetrate across the profession. Method: Databases searched were Ovid Medline, EMBASE, AMED and CINAHL. Search terms were selected after gaining understanding of the topic: occupational therap* AND Exp burnout / OR Exp morals / OR retention OR clinical reasoning OR new graduate OR novice OR transition-to-practice. Studies were critically appraised using the criteria of credibility, transferability, confirmability and dependability. Findings, along with direct quotes, were extracted and data compared and contrasted through first, second and third order analysis. Findings: Twenty-four studies were included in the meta-synthesis and three constructs were identified: 'challenges in context'; 'personal challenges' and 'social and cultural challenges'. These findings inform knowledge about constraining factors on clinical reasoning and the alignment of practice with the occupational therapy philosophy, and give insight into satisfaction with practice, ethical and professional behaviours. Conclusion: These findings could inform provision of professional support, education for students and enhance agency to reform practice. More research is needed about professional socialisation, clinical reasoning and ethical issues.